National-standard middle-distance runners maintain 1500 m time trial running performance on successive days - Birdsey, L. P.; Brown, S.; Dos`Santos, T.; Evans, D.; Runacres, A.; Weston, M.; Field, A. (European Journal of Sport Science, 2026)
To examine how middle-distance athletes maintain self-paced time trial performance on successive days, 12 national-standard middle-distance specialists performed two self-paced 1500 m time trials on successive days. Following baseline assessment and familiarisation trials, participants (10 male, 2 female, mean age ± SD: 27 ± 7 years, mass: 66 ± 8 kg, height: 1.80 ± 0.08 m, season best 1500 m time: 243.9 ± 18.4 s) performed two 1500 m time trials separated by 24 h on an instrumented treadmill. Internal (respiratory exchange ratio; RER, oxygen uptake, blood lactate concentration, heart rate, session and differential ratings of perceived exertion) and external (speed and time) measures quantified exercise intensity. Step length and frequency were collected from integrated force transducers (1000 Hz). All variables were log transformed before analysis with mixed linear models. The uncertainty (90% confidence interval) of our between-trial differences (trial 2 vs. trial 1) for all measures other than peak and mean RER were equivalent to previously reported measurement errors. Additionally, athletes were ~2.5 times more likely to perceive greater exertion for time trial two, but with considerable uncertainty around the estimates. National-standard middle-distance specialists maintain 1500 m time trial running performance on successive days without the use of any structured recovery interventions.